Advanced Sensorless Control of Brushless DC Motor using Terminal Voltage Sensing Method - Sumathi, E; Sheela, M. Santhosh; kumar, B. Arun (International Journal of Computer Sciences and Engineering, 2014)
Brushless DC (BLDC) motor drives are popularly used in both consumer and industrial applications owing to its compact size, controllability and efficiency. BLDC motor is usually operated with one or more rotor position sensors, since the electrical excitation must be synchronous to the rotor position. To reduce cost and complexity and also to improve reliability of the drive system, sensorless drive is preferred. This paper presents the development of sensorless control system for brushless DC motor using terminal voltage sensing method without using any position sensors such as hall sensors or encoders. The simulation for proposed system is done using MATLAB.